Functional tricuspid regurgitation : a clustering analysis and prognostic validation of 3 phenotypes on an external cohort. (4th February 2022) - Vely, M; L"official, G; Galli, E; Lacout, M; Leurent, G; Oger, E; Donal, E
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Functional tricuspid regurgitation (FTR) ≥ moderate is an independent risk factor of morbidity and mortality. FTR could be classified into 2 categories: "atrial functional-TR" (AF-TR) and "ventricular functional-TR" (VF-TR). Percutaneous procedures increase interest in best understanding and selecting patients eligible for intervention. We aim to study echocardiographic criteria associated with the prognosis in patients with severe TR, using a clustering method on a retrospective monocentric cohort that we applied to an external validation prospective multicentric cohort. Methods and results: Ninety-two patients with severe TR (mean age 77.9 ± 13 years, 48.9% female, atrial fibrillation in 68.5%) were enrolled. A hierarchical clustering analysis was conducted. Four parameters explained the clustering categorization (right ventricular (RV) end-diastolic mid-cavity diameter, RV free-wall Strain, right atrial (RA) volume index, RA Strain; p = 0, 0039). Three clusters were identified: Cluster 1 with better right ventricular, left ventricular, and right atrial function (related to AF-TR) compared with Cluster 2 (related to VF-TR). Cluster 3 includes patients with severely dilated heart chambers, and RV and RA dysfunction. When applying the 3 clusters in the validation cohort (149 patients), the primary endpoint (hospitalization for Heart failure and/or death from any cause) was significantly better in cluster 1 in 30.8% versus 48% and 58.8% in clusters 2 and 3 respectively (p < 0.05). Conclusion: Three phenotypes of FTR were built.  Significant TR assessment should include RV and RA characteristics. AF-TR seems to have a better prognosis than VF-TR (under non interventional management).